Usability engineering scenario-based development of human-computer interaction - Rosson, Mary Beth.; Carroll, John M. (John Millar), 1950- (San Fancisco : Academic Press, 2002)
You don't need to be convinced. You know that usability is key to the success of any interactive system-from commercial software to B2B Web sites to handheld devices. But you need skills to make usability part of your product development equation. How will you assess your users' needs and preferences? How will you design effective solutions that are grounded in users' current practices? How will you evaluate and refine these designs to ensure a quality product? Usability Engineering: Scenario-Based Development of Human-Computer Interaction is a radical departure from traditional books that emphasize theory and address experts. This book focuses on the realities of product development, showing how user interaction scenarios can make usability practices an integral part of interactive system development. As you'll learn, usability engineering is not the application of inflexible rules; it's a process of analysis, prototyping, and problem solving in which you evaluate tradeoffs, make reasoned decisions, and maximize the overall value of your product. * Written by prominent HCI educators who understand how to teach usability practices to students and professional developers. * Interleaves HCI theory and concepts with a running case study demonstrating their application. * Gradually elaborates the case study to introduce increasingly sophisticated usability engineering techniques. * Analyzes usability issues in realistic scenarios that describe existing or envisioned systems from the perspective of one or more users. * Emphasizes the real world of usability engineering-a world in which tradeoffs must be weighed and difficult decisions made to achieve desired results. * Includes a companion Web site which provides additional case studies in a multimedia format, along with a Java application for creating and editing scenarios. This site also provides instructors with sample syllabi, lecture slides and notes, in-class exercises, solutions to textbook exercises, additional project ideas, and links to other HCI resources.
Scenario-based usability engineering -- Analyzing requirements -- Activity design -- Information design -- interaction design -- Prototyping -- Usability evaluation -- User documentation -- Emerging paradigms for user interaction -- Usability engineering in practice.
Includes bibliographical references and index.
Keywords: Human-computer interaction; User-centered system design; Electronic books